De Aeschyli Amymona satyrica - Cipolla , Paulus B. (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2020)
The paper offers a survey of Aeschylus’ satyr drama Amymone, which was staged probably in 463 BC together with the trilogy of the Danaids. After discussion on the argument of the play and its possible reconstruction, the three surviving fragments are presented with critical text, Latin translation and thorough commentary.